Fine-tuning SLE treatment: the potential of selective TYK2 inhibition - Yoshiya Tanaka; Shingo Nakayamada; Yurie Satoh-Kanda (RMD Open)
In systemic lupus erythematosus (SLE), adaptive immunity is activated by the stimulation of innate immunity, leading to the development of autoreactive T cells and activation and differentiation of B cells. Cytokine signalling plays an essential role in the pathogenesis and progression of this disease. In particular, the differentiation and function of CD4+ T cell subsets, which play a central role in SLE pathology, are significantly altered by cytokine stimulation. Many cytokines transmit signals via the Janus-activated kinase (JAK)-STAT pathway, but there is no one-to-one correspondence between cytokine receptors and JAK/TYK2. Multiple cytokines activate JAK/TYK2, and multiple JAK/TYK2 molecules are simultaneously activated by a single cytokine. Therefore, the modulation of the JAK-STAT pathway has the potential to control immune responses in SLE. Although several JAK/TYK2 inhibitors are currently undergoing clinical trials, more selective drugs that can target cytokine signals according to the specific pathology of the disease are required. TYK2 inhibitors, which are involved in the signal transduction of type I interferon and interleukin-12/23 pathways and are linked to disease susceptibility genes in SLE, may have the potential to fine-tune the differentiation and function of immune cells, particularly CD4+ T cells.